Adopting Knowledge Management Mechanisms: Evidence from Portuguese Organizations. (8th August 2014) - Oliveira, Mirian; Maçada, Antonio Carlos Gastaud; Curado, Carla
<x xml:space="preserve">Abstract</x> In the following paper, we propose that organizations will favor a particular mode of knowledge conversion when considering which knowledge management (KM) mechanisms to adopt. There is a gap in the research regarding the relationship between adoption of KM mechanisms, modes of knowledge conversion and the KM elements (people, process and technology). Thus, the main objective of this paper is to associate KM mechanisms with the modes of knowledge conversion and KM elements. The method adopted was a multiple‐case study involving 11 organizations acting in Portugal. Data collected during interviews were subsequently subjected to content analysis. The study contributes to the literature by offering propositions regarding the association between KM mechanisms and modes of knowledge conversion. The results suggest KM mechanisms should be adopted according to the stages of KM implementation. This study may also serve as a guide for organizations when choosing which KM mechanisms to adopt. Copyright © 2014 John Wiley & Sons, Ltd.